Autoantibody clusters in rheumatoid arthritis are not driven by antigen specificity or isotype - Johan Rönnelid; Diane van der Woude; René E M Toes; Solbritt Rantapää-Dahlqvist; Heidi Kokkonen; Linda Johansson; Rachel Knevel; Tineke J van Wesemael; Marc P Maurits; Anouk G van Mourik (RMD Open)
Objective Autoantibodies are a key feature of rheumatoid arthritis (RA). They can be detected years before disease onset, but it is unknown if there is any pattern in the co-occurrence of antigen recognition or isotype profiles. A common signature could point to a unique initial trigger for autoantibody development. Therefore, we sought to determine if there is a pattern in antigen or isotype reactivity in pre-symptomatic cases and established RA.Methods One pre-symptomatic cohort and one RA cohort were analysed for the co-occurrence of different isotypes of anti-modified protein antibodies (AMPA) and rheumatoid factor (RF). Patterns in autoantibody levels were investigated with clustering. Additionally, total IgG was measured in 1- year follow-up sera of a representative subgroup of the RA cohort.Results While especially anti-citrullinated protein antibodies (ACPA) IgG and RF IgA co-occurred with other autoantibodies, no specific patterns emerged. In both cohorts, clusters of autoantibody levels were not determined by particular antigen reactivities or isotype. However, clusters were driven by elevated levels of several different AMPA, with distinct AMPA high- and low-level clusters. A broad IgG autoantibody profile was not accompanied by high total IgG levels.Conclusion Autoantibody clusters are most likely not driven by AMPA specificity or isotype profile, neither before nor at RA onset, but are instead determined by a broad variety of autoantibodies. This indicates that the triggers for autoantibody development in RA do not skew the response towards certain autoreactivities or isotypes but rather lead to a broad and diverse autoantibody repertoire reflecting continuous and ongoing immune activation.